A mathematical model for degradation of forest area by industrialization causing migration of wildlife species - Jatav, Shikha; Sundar, Shyam; Malviya, Alok (Nonlinear Analysis: Modelling and Control, 2025)
This study presents a nonlinear mathematical model incorporating four key variables: forest area, biomass density, industrialization level, and wildlife population. The model assumes that biomass is proportional to forest area and that wildlife density depends on biomass availability. Our analysis demonstrates that increasing industrialization leads to significant forest depletion, which in turn accelerates wildlife migration. The results highlight critical thresholds beyond which forest degradation becomes irreversible, emphasizing the urgent need for sustainable industrial policies and conservation strategies. Numerical simulations and sensitivity analysis validate the model outcomes and provide insights for ecological preservation.
Keywords: forest area; industrialization; migration; wildlife species; stability analysis